Towards Flexible Creation of Multi-Level Models - Töpel, Daniel; Kaczmarek-Heß, Monika (ACM/IEEE 25th International Conference on Model Driven Engineering Languages and Systems: Companion Proceedings. ACM, 2022)
A process of a multi-level model creation follows typically the topdown approach, i.e., it requires first defining concepts and relations on the highest classification levels, which only then can be used to create concepts on the lower ones. Empirical insights into the process of multi-level model creation suggest however, that this strategy may be counter-intuitive and challenging, especially for non-experts. This paper addresses this problem by focusing on the idea of flexible multi-level model creation, understood as an intertwined application of top-down and bottom-up strategies. As a first step towards realizing this vision for multi-level models in general, and those created with the XModeler and Flexible MetaModeling and Execution Language (FMMLx) in particular, in this paper, we select a set of relevant multi-level refactoring patterns, adapt them to our approach, and implement them in the supporting tool. We illustrate the flexible creation process using an exemplary scenario.